Nurse managers in mental health units: from activities to time management - Alferes, Luísa Paula da Silva Pires; Martins, MM; Reis Santos, Margarida; Teixeira, Manuela; Poeira, Ana Filipa da Silva; Pires, Regina; Asseiro Alferes, Rui Paulo (Universidade Federal do Ceará Departamento de Enfermagem Rede de Enfemagem do Nordeste, 2022)
Objective: to understand the use of time by nurse managers in psychiatry and mental health units, as they carry out their daily tasks. Methods: cross-sectional study, carried out by 48 managers from public psychiatric units and from the social sector. Data collection was made through an online questionnaire that is part of the Scale of Perception of Nurse Manager Work, including 43 items separated in five functional domains of nurse managers. The responses were in a Likert scale: does not take time, takes little time, takes some time, takes much time. Results: the activities inherent to ethical and legal professional practices and to the management of care and of human resources required more time from the manager when compared to policy interventions, and consulting and professional development. Conclusion: the managers recognize that managing time implies organization, planning work, and establishing priorities in the tasks to be developed.

Objetivo: compreender a utilização do tempo dos gestores de enfermagem em unidades de Saúde Mental e Psiquiatria no desempenho das atividades diárias. Métodos: estudo transversal, constituído por 48 gestores de unidades psiquiátricas públicas e do setor social. Coleta de dados por meio de questionário online que integrava a Escala de Percepção do Trabalho dos Gestores em Enfermagem, inclui 43 itens, distribuídos por cinco domínios funcionais dos enfermeiros gestores. Respostas cotadas em escala tipo Likert: não ocupa tempo; ocupa pouco tempo; ocupa algum tempo; ocupa muito tempo. Resultados: as atividades inerentes às competências prática profissional ética e legal, e gestão de cuidados e de recursos humanos consumiam mais tempo ao gestor comparativamente com intervenção política e assessoria e desenvolvimento profissional. Conclusão: os gestores reconhecem que gerir o tempo implica organização, planejamento do trabalho e estabelecer prioridades nas tarefas a desempenhar.
Gestor de Enfermagem em unidades de saúde mental: das atividades à utilização do tempo
Keywords: Enfermagem; Saúde Mental; Gestor de Saúde